Effect of Guided Discovery Teaching Strategy on Grade 9 Students Self-Efficacy and Performance in Science - Yogaranee, S. (My University, 2016)
This study sought to investigate the effect of teaching strategies on self-efficacy and science achievements of students. One hundred and forty seven students who were in grade nine in Tamil medium schools located in Colombo South Educational Zone in Sri Lanka took part in this study. A quasi-experimental non-equivaleant group pretest-posttest design was used to examine ...
Keywords: Effect of Guided Discovery Teaching Strategy on Grade 9 Students Self-Efficacy and Performance in Science